2006
DOI: 10.1007/s11207-006-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AlF Molecular Lines in Sunspot Umbral Spectra

Abstract: High resolution FTS sunspot umbral spectra from NSO/Kitt Peak were used to detect rotational lines due to 11 electronic transitions of the molecule AlF, in the wavelength region 4400 -9000Å. The presence of lines due to bands C -A (0,0), (0,1), (0,2) and (1,2), D -A (0,0) and (0,1), F -A (0,0), G -A (0,0), and F -B (0,0) is confirmed. Further, the presence of lines due to C -A (1,0) and (1,1) transitions is treated as doubtful because of heavy blending in the region, by rotational lines of TiO. Among the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Also, Highberger et al (2001) reported in 2001 the detection of AlF in the circumstellar envelope of the so-called Egg Nebula (CRL 2688). Following the suspected presence of AlF in umbral spectra suggested by the observations of Wöhl (1971) and using the significant values of transition probabilities computed by Murty (1977), Joshi et al (1982) and Balachandra Kumar et al (2002Kumar et al ( , 2003Kumar et al ( , 2004, Bagare et al (2006) have conducted a fresh search for the presence of AlF lines with the high resolution FTS sunspot umbral spectra. They reported without doubt that the bands of AlF are present in the umbral spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Highberger et al (2001) reported in 2001 the detection of AlF in the circumstellar envelope of the so-called Egg Nebula (CRL 2688). Following the suspected presence of AlF in umbral spectra suggested by the observations of Wöhl (1971) and using the significant values of transition probabilities computed by Murty (1977), Joshi et al (1982) and Balachandra Kumar et al (2002Kumar et al ( , 2003Kumar et al ( , 2004, Bagare et al (2006) have conducted a fresh search for the presence of AlF lines with the high resolution FTS sunspot umbral spectra. They reported without doubt that the bands of AlF are present in the umbral spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The values of slopes being equal to Bhc/2.3kT , the corresponding temperatures (T ) were estimated for bands A 2 -X 2 + (0, 0), B 2 + -X 2 + (0, 0; 1, 1; 2, 2) to be 2641 K, 2592 K, 1738 K and 1737 K respectively. The effective rotational temperatures had been estimated for D-A (0,0) and F -A (0,0) bands of AlF to be 1240 ± 120 K and 2390 ± 400 K respectively by Bagare et al (2006). Mulchaey (1989) has estimated the average temperature of the FeH molecule for the two P(J ) branches of the (7/2)-(7/2) sub-band to be 1740 ± 100 K. The lower value of T (1737 K) evaluated for SrF in the present study is therefore similar to that of the B 2 + -X 2 + (0, 1) band of LaO reported by Sriramachandran et al (2008) and of FeH (Mulchaey 1989).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the molecular bands due to AlF can be used as a good diagnostic for the purpose. Bagare et al (2006) have studied the presence of AlF in spectra of sunspots and have recommended a wavelength range which can be used to search for the presence of AlF in stellar spectra. In addition to the importance of F as a product of AGB stars, Sr is also found reported as an important s-process element which is known to be anomalous in the solar nebulae.…”
Section: Introductionmentioning
confidence: 99%
“…We are used to hearing about typical temperatures of 4,500-6,000 K in sunspots, but much lower values have been inferred in absorbing layers of molecular lines in sunspot umbrae, as low as 1,240 K (Bagare et al 2006).…”
Section: Sunspotsmentioning
confidence: 99%